Development and measurement of the transverse diameter of the fetal cerebellum by MRI - Farinha, Cristina (2014)
Fetal magnetic resonance imaging (MRI) is an effective method in the prenatal evaluation of normal brain morphology and diagnosis of diseases of the central nervous system. It is an important complement to clinical ultrasound. The cerebellum is one of the least affected structures in cases of fetal growth restriction, so it is a good index for evaluating fetal development and gestational age. Thus, biometric evaluation is essential in fetal prenatal diagnosis of brain development. Purpose – Evaluation of the transversal cerebellum diameter (the anatomical structures reference of the fetal central nervous system) and compare it with an international reference study in this regard. Material and methods – The sample consisted of 84 pregnant women who have performed magnetic resonance in a medical imaging clinic in the Centre region. The average considered for evaluating fetal development was the transversal cerebellum diameter. Results – The results for the transversal cerebellum diameter demonstrate the absence of statistically significant mean differences (p>0.05) in the number of weeks of gestation compared with theoretical values measured in the study by Garel. Conclusion – Based on the obtained results we can conclude that the parameter analyzed is consistent with the publication of Catherine Garel – Le développement du cerveau foetal atlas IRM et biometrie.